Physiological, nutritional, and biochemical indicators of lead tolerance in sunflower genotypes - Ribeiro, Marcos de Oliveira; Azevedo Neto, André Dias de; Cova, Alide Mitsue Watanabe; Ribeiro, Lucas de Oliveira; Menezes, Renata Velasques; Abreu, Claudia Brito de; Dias, Fábio de Souza; Silva, Petterson Costa Conceição; Gheyi, Hans Raj (Semina: Ciências Agrárias, 2022)
This study aimed to select and classify sunflower genotypes tolerant to lead (Pb) stress and evaluate their capacity of phytoextraction based on physiological, nutritional, and biochemical responses. Two experiments were carried out under lead stress. In the first experiment, out of 21 genotypes studied three showed higher relative biomass yield and were characterized as Pb-tolerant and five showed lower relative biomass production and were considered Pb-sensitive. In the second experiment, one Pb-tolerant (BRS-G27) and two Pb-sensitive (H251 and AG963) genotypes were studied. In this experiment, Pb stress reduced the growth and contents photosynthetic pigments in all genotypes, but more pronouncedly in sensitive genotypes. There were no substantial changes in micronutrient levels in the leaves and stem, but the levels of Cu and Mn in the stressed roots of sensitive genotypes were much lower than in BRS-G27. The contents of organic solutes in the roots suggest that sensitive genotypes have higher energy costs for osmoregulation by carbohydrates and amino acids synthesis. However, the accumulation of proline may be related to a greater Pb tolerance. Considering the results of dry mass yield, transfer coefficient, translocation factor, and tolerance index, the BRS-G27 genotype can be recommended for use in phytoremediation of Pb-contaminated soils.